Biomechanics of competitive front crawl swimming. - Toussaint, H. M.; Beek, P. J. (Sports Medicine, 1992)
Essential performance-determining factors in front crawl swimming can be analysed within a biomechanical framework, in reference to the physiological basis of performance. These factors include: active drag forces, effective propulsive forces, propelling efficiency, and power output.